Letter - Pankhurst, E. Sylvia (Estelle Sylvia), 1882-1960
010-0119-001 NEW TIMES & ETHIOPIA NEWS "WEST DENE," 3 CHARTERIS ROAD, WOODFORD GREEN, ESSEX, ENGLAND. Editor: E. SYLVIA PANKHURST Telephone: BUCkhurst 2463 August 28th, 1936. The Secretary, National Council of Labour, Transport House, Smith Square, S.W.1. Dear Secretary, Is the attached appeal authorised? I am sorry I cannot read the signature. Yours sincerely, E. Sylvia Pankhurst 292/946/10/129